INTEGRATION OF CO-OPERATIVE EDUCATION INTO THE MERAH PUTIH CO-OPERATIVE POLICY TO ACHIEVE THE WELFARE OF RURAL COMMUNITIES - Zamzami Zamzami; Jasmadi; Usman (Jurnal Ikhtibar Nusantara, 2026)
The Koperasi Merah Putih is designed as an instrument of people-centered economic development that emphasizes the principles of mutual cooperation, participation, and village self-reliance. This study aims to analyze the implementation of Presidential Instruction Number 9 of 2025 on the Koperasi Merah Putih in realizing the welfare of village communities. The research employs a qualitative method with a descriptive approach, using in-depth interviews, participatory observation, and documentation studies. Data are analyzed through the interactive model of Miles, Huberman, and Saldaña, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the government policy has a clear direction and is relevant to village needs, although consistency of implementation at the local level varies. Cooperative institutions have been formally established, yet they still face constraints related to managerial capacity and weak accountability. Community participation in cooperatives remains relatively low, influenced by limited financial literacy and a lack of sense of ownership. From an economic empowerment perspective, cooperatives provide access to capital, entrepreneurship training, and market opportunities, although the benefits have not been evenly distributed. Tangible impacts include increased member income, reduced dependence on moneylenders, and strengthened social solidarity, even though these effects are still limited to certain areas. Therefore, this study affirms that the success of Presidential Instruction No. 9 of 2025 is strongly determined by the strengthening of cooperative governance, enhancement of human resource capacity, community participation, and sustained regulatory and financial support. The Koperasi Merah Putih has significant potential to become a driving force for village development if managed in a transparent, accountable, participatory, and sustainable manner.